PENGEMBANGAN MEDIA KARTU BERSERI UNTUK MENINGKATKAN MINAT MEMBACA SISWA KELAS III SDN 105385 KOTASAN - Khoirunnisyah; Arrini Shabrina Anshor; Abdul Mujib; Risnawaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce valid, practical, and effective serial card media to increase students' interest in reading. The research method uses the development model EDDIE. The subjects of the study were 22 third-grade elementary school students and the object of the study was serial card media in Indonesian language learning on short story material. Data collection instruments were material expert questionnaires, media expert questionnaires, student response questionnaires, teacher response questionnaires, reading interest questionnaires, and pretest-posttest. Data analysis techniques were data descriptions and percentages. The validation results by material experts obtained 95%, media experts 100%, and evaluation experts 89.28% with a very valid category. The practicality test showed that the serial card media was very practical to use by students and teachers with a practicality score of 91.25% from student responses and 94.23% from teacher responses. The effectiveness of the media was demonstrated through an increase in students' reading ability with an N-Gain value of 0.64 in trial I to 0.67 in trial II. The increase in students' reading interest in trial I was 65% before learning, then increased to 85% after learning. Furthermore, in trial II, students' reading interest before learning was 71%, and increased to 94.5% after learning. This indicates that the serial card media is valid, practical, and effective and can increase students' reading interest.